Propagação, metabolismo secundário e genotoxicidade de Solidago chilensis Meyen (Asteraceae) - Löbler, Lisiane (2013)
Native medicinal plants are widely used, but are insufficient scientific information on the spread of some species and cytotoxicity. This study investigated the sexual propagation and vegetative species Solidago chilensis Meyen (Asteraceae) through seed germination, micropropagation, cuttings, evaluate the genotoxic and quantify the accumulation of secondary metabolites of plants obtained. Studies of germination in vitro and ex vitro seeds were developed by testing storage conditions, concentrations of gibberellic acid (GA3), light regimes, soaking times in water to 5ºC ± 1ºC, temperatures and populations. For micropropagation were used apical and nodal segments and combinations of benzylaminopurine BAP (0,0 e 2,0 mg L-1) and naphthalene acetic acid NAA (0,0 e 0,2 mg L-1). In the study of stem cuttings were used cuttings of branches overhead and underground rhizomes. Apical, middle and basal branches were kept in distilled water and nutrient solutions Murashige and Shoog (20%), with or without indole butyric acid (IBA) (5,0 mg L-1). For the cutting of rhizomes, segments thereof were immersed in 0, 600 and 1200 mg L-1 IBA for six hours and after cultured in Plantmax, sand or vermiculite. Apical leaves from four different origins: natural plants growing in wasteland; plants from wasteland and cultivated in the greenhouse, plants from cuttings and rhizomes micropropagated plants were collected for the assessment of genotoxicity and quantification of total polyphenols and flavonoids by spectrophotometry, and chlorogenic acid, quercetin and rutin by High Performance Liquid Chromatography Efficiency. The genotoxicity was assessed using the Allium cepa test, testing concentrations of 5 and 20 g L-1 aqueous extracts of dried leaves. Populations influenced the germination of seeds, and the wasteland of the ones who had averaged 57,2% germination. The seeds germinated under 16h photoperiod (2,4% and 22,3%) and continuous darkness (3,5% and 17,6%). The soaking time of 36 hours favored germination (56% and 24,7%) and germination rate in the experiment 2 and 3, respectively. A temperature of 20°C, in experiment 3, provided the highest percentage of seed germination, 26,6%. In micropropagation, the combination of 2,0 mg L-1 of BAP and 0,2 mg L-1 og NAA, provided 49% of complete plants and 37% survival at acclimatization. In cuttings of new shoots, rooting in the substrate occurred over water with the presence of IBA (29%). The Plantmax® provided 62% rooting in cuttings of rhizomes did not differ from sand (43%). In the evaluation of genotoxicity was detected genotoxic potential of extracts derived from micropropagated plants (5 and 20 g L-1) and grown in a greenhouse (5 g L-1). Polyphenols and flavonoids were found in all the extracts and identified flavonoids quercetin and chlorogenic acid in higher concentrations in plants of wasteland, 441,4 and 95,7 mg g-1, respectively, and rutin in similar concentration in all samples (mean 46,9 mg g-1).